2013
DOI: 10.1103/physrevc.88.014905
|View full text |Cite
|
Sign up to set email alerts
|

Physics probed by thePTdependence of the nuclear suppression factor

Abstract: The nuclear suppression factor R AA of single inclusive hadrons measured in ultrarelativistic heavy-ion collisions was the first observable to study jet quenching, i.e., the final state interaction of hard parton showers with the surrounding bulk matter. While its transverse momentum (P T ) dependence of R AA observed at RHIC was weak and hence never decisive in constraining models, there is now a strong and nontrivial P T dependence observed at the LHC. This has been a challenge for several models which worke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 34 publications
(64 reference statements)
3
45
0
Order By: Relevance
“…Though many models can describe the observed jet quenching at RHIC quite well by adjusting parameters, there exist differences in the implementation of parton energy loss in jet quenching models [49]. New data from LHC experiments have lent support to some of these models [50][51][52] while challenging others [26,27,53]. Even within those models that can describe experimental data, the combined data from experiments at RHIC and LHC provide unprecedented constraints on the medium parameters as probed by jet quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Though many models can describe the observed jet quenching at RHIC quite well by adjusting parameters, there exist differences in the implementation of parton energy loss in jet quenching models [49]. New data from LHC experiments have lent support to some of these models [50][51][52] while challenging others [26,27,53]. Even within those models that can describe experimental data, the combined data from experiments at RHIC and LHC provide unprecedented constraints on the medium parameters as probed by jet quenching.…”
Section: Introductionmentioning
confidence: 99%
“…YaJEM, however, exhibits a slightly steeper increase with jet p T than the data. [8] and JEWEL [9]. The boxes at R AA = 1 represent the systematic uncertainty on < T AA >.…”
Section: Jet Nuclear Modification Factormentioning
confidence: 99%
“…The first model, YaJEM [8], uses a 2+1D hydrodynamical model to calculate medium transport coefficients which describe the coupling between partons and medium and modify the kinematics of the virtual partons in the evolving parton shower through an increase in virtuality. The second model, JEWEL [9], models energy loss in the presence of a QCD medium microscopically through multiple scattering and gluon radiation, including a Monte Carlo (MC) implementation of LPM interference effects.…”
Section: Jet Nuclear Modification Factormentioning
confidence: 99%
“…directly images ǫ n in position space. While it can be shown that the energy degradation of the leading parton peaks between 1-2 fm/c [3], it is also known that high P T v 2 has sensitivity to late time dynamics which may reach well into the hadronic phase around 5-7 fm/c [4].…”
Section: Introductionmentioning
confidence: 99%